An Infrastructure to Advance the Scholarly Work of Staff Nurses - Parkosewich, Janet A. (YJBM, 2013)
The traditional role of the acute care staff nurse is changing. The new norm establishes an expectation that staff nurses base their practice on best evidence. When evidence is lacking, nurses are charged with using the research process to generate and disseminate new knowledge. This article describes the critical forces behind the transformation of this role and the organizational mission, culture, and capacity required to support practice that is based on science. The vital role of senior nursing leaders, the nurse researcher, and the nursing research committee within the context of a collaborative governance structure is highlighted. Several well-known, evidence-based practice models are presented. Finally, there is a discussion of the infrastructure created by Yale-New Haven Hospital to advance the scholarly work of the nursing staff.